FIB-4 index serves as a noninvasive prognostic biomarker in patients with hepatocellular carcinoma: A meta-analysis - Zhang, Yi (Medicine (Baltimore), 2018)
BACKGROUND: Liver fibrosis index FIB-4 has been reported to be linked with hepatocellular carcinoma (HCC) prognosis, but the results were not consistent. This study aimed to synthetically explore the relationship between FIB-4 and clinical outcomes of HCC. METHODS: A number of online databases were searched for relevant articles published before March 1, 2018. Hazard ratios (HRs) with 95% confidence intervals (95% CIs) were calculated to assess the prognostic value of the FIB-4 index in patients with HCC using Stata SE 12.0. RESULTS: Eight articles (including 10 cohort studies) with 3485 HCC patients were finally included for analysis. The pooled results showed that FIB-4 index was significantly associated with overall survival (OS) for patients with HCC (HR = 1.74, 95% CI: 1.41–2.07, P <.001). And HCC patients with higher FIB-4 score were at significantly greater risk of recurrence 1.53 (95% CI: 1.29–1.78, P <.001). Subgroup analysis based on the treatment, stage and analysis type also confirmed the prognostic values of the FIB-4 score for OS and recurrence-free survival (RFS) in HCC. CONCLUSIONS: FIB-4 index might be a useful predictive marker in patients with HCC.